MODERN SCULPTURE ART OF UZBEKISTAN AS NATIONAL VALUES - Cho’ponova Sabrina Xolnazarovna (TADQIQOTLAR.UZ, 2024)
Annotation: In this article, in the new historical period that began in Uzbekistan, significant creative changes in the art of sculpture, as well as the formation of a healthy spiritual and cultural environment in the country as a new cultural policy, as well as national traditions issues of restoration, understanding of our historical and cultural identity are covered.